Quantitative Analysis of Isometric Ankle Torque and Muscle Activity during Dorsiflexion and Plantarflexion - A. Almasiri, Osamah A.; Buniya, Ali K.; Abdul-Ameer, Hussam K. (Al-Khwarizmi Engineering Journal, 2024)
Foot and ankle movements are essential in various activities like walking, running, and balance, where the mechanics of these movements are affected by the muscles around the ankle joint [1,2].  In this study, the correlations between isometric ankle torque and muscle activity of the tibialis anterior (TA) and gastrocnemius (GAS) in the course of dorsiflexion and plantarflexion was investigated. Eight healthy participants were enrolled for the study, where the ankle torque and surface Electromyography (sEMG) of the main flexors were measured and analyzed. The results showed that ankle torque is higher in plantarflexion than dorsiflexion. In addition, the TA has greater muscle activity during dorsiflexion, while the GAS presents higher activity through plantarflexion. Additional investigation using power spectrum density analysis of the recorded sEMG was conducted and it shows the influence of fast twitching muscles on the isometric ankle torque. The outcomes of this work have the potential for developing and assessing new rehabilitation strategies.